2019
DOI: 10.14740/jocmr3744
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Use of Thiazide Diuretics and the Risk of Skin Cancers: A Meta-Analysis of Observational Studies

Abstract: BackgroundThiazide diuretics are among the most widely prescribed antihypertensive agents. Given their photosensitizing effects, however, there are concerns that they may increase the risk of skin cancers. In this meta-analysis, we investigated an association between the use of thiazide diuretics and the risk of skin cancers.MethodsWe identified studies by searching three electronic databases (PubMed, EMBASE, and the Cochrane Library) from their inception to October 30, 2017. Nine relevant observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 41 publications
1
50
1
3
Order By: Relevance
“…Thiazide diuretics are known to possess photosensitising properties 7 ; in 2013, the International Agency for Research on Cancer classified HCTZ as “possibly carcinogenic to humans” (Group 2B) 8 . Recent studies reported HCTZ increased the risk of developing a range of skin cancers, particularly squamous cell carcinomas (SCCs), 2,7,9‐13 and warnings from medicines regulatory agencies in Europe, 14 the UK, 15 Canada, 16 Singapore 17 and New Zealand 18 followed from October 2018. These findings and regulatory warnings are particularly relevant for Australia, which has the highest incidence of skin cancer in the world 19…”
Section: Introductionmentioning
confidence: 99%
“…Thiazide diuretics are known to possess photosensitising properties 7 ; in 2013, the International Agency for Research on Cancer classified HCTZ as “possibly carcinogenic to humans” (Group 2B) 8 . Recent studies reported HCTZ increased the risk of developing a range of skin cancers, particularly squamous cell carcinomas (SCCs), 2,7,9‐13 and warnings from medicines regulatory agencies in Europe, 14 the UK, 15 Canada, 16 Singapore 17 and New Zealand 18 followed from October 2018. These findings and regulatory warnings are particularly relevant for Australia, which has the highest incidence of skin cancer in the world 19…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed a possible association between labial squamous cell carcinoma and the exposure to this thiazide, in 633 cases compared to 63,067 controls, with a cumulative dose-response relationship with adjusted OR of 2.1 (95% CI : 1.7-2.6) which increased up to OR 3.9 (3.0-4.9) for patients who used it at high dose (~ 25.000 mg) and a OR 7.7 (5.7-10.5) for the highest cumulative dose (~ 100,000 mg) [33]. Finally, a recent study, conducted with the evaluation of different databases (PubMed, EMBASE, Cochrane Library), would confirm the association with increased risk of skin cancers, especially squamous cell carcinoma (underlining the need for further studies to confirm the results) [34]. The AIFA report concluded the report by inviting the physicians to the following prescriptive behaviors and to adopt the following precautions: information on the risk of non-melanoma skin cancers for patients taking hydrochlorothiazide, alone or in combination with other drugs, with the regular control and self-control of the skin for the early identification of any new lesions or changes to existing lesions, with notification to your doctor of any suspected skin lesion; examination of suspected skin lesions both from a clinical but also histological point of view, using the bioptic exam; warning patients about the limitation of exposure to sunlight/UV rays, with the use of adequate protection when exposed to sunlight/UV rays, to minimize the risk of skin cancers; careful evaluation and discernment on the prescription/use of hydrochlorothiazide in patients who have had a previous skin cancer.…”
Section: Known Adverse Events Of Hydrochlorothiazidementioning
confidence: 92%
“…37 The recent north European nationwide case control study by Pedersen et al found a clear doseresponse relationship between hydrochlorothiazide use and both BCC and SCC, especially the latter cancer type. 5 In this analysis, the use of high 39 It must be pointed out that this analysis is based on few and generally heterogeneous observational studies for every type of skin cancer and many of these studies do not consider the interaction between different skin types, sun exposure and family history of skin cancer. Despite this, the association between thiazide diuretics and SCC risk appears to be supported by the epidemiological evidence available to date.…”
Section: Skin Cancermentioning
confidence: 99%